PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MATERI NILAI-NILAI PANCASILA KELAS IV SDN 182 PEKANBARU - Hutasoit, Helena Okti Marito; Hadikusuma Ramadan, Zaka (STKIP Subang, 2026)
This study aims to develop an animated video–based learning medium for teaching Pancasila values to fourth-grade elementary school students. The study employed a research and development method using the ADDIE model. The research subjects consisted of a fourth-grade teacher and students at SDN 182 Pekanbaru, as well as six validators, including two material experts, two language experts, and two media experts. Data were collected through interviews and questionnaires, while data analysis was conducted using qualitative and quantitative approaches. The validation results showed that the animated video learning media achieved a validity percentage of 96.73% for the content aspect, 91.23% for the language aspect, and 87.5% for the media aspect, all of which fell into the very valid category. In addition, the teacher response reached 100%, and the student response reached 84.72%, both of which were categorized as very good. Based on these findings, it can be concluded that the developed animated video learning media is feasible for use in learning activities and can help improve students’ understanding and learning interest in Pancasila values at the elementary school level.